Characterization of the complete chloroplast genome of Malus spectabilis ‘Guanghui’ - Qiqing Jiao; Jihan Tao; Chuanzeng Wang; Yanlei Yin; Lijuan Feng (Mitochondrial DNA. Part B. Resources, 2020)
Malus spectabilis ‘Guanghui’ is an important ornamental plant, which complete chloroplast genome (Accession: MT501657) was sequenced, assembled and annotated. The genome size is 1601,230 bp and the overall GC content is 36.50%, with large single-copy (LSC, 89,310bp) regions, small single-copy (SSC, 19,196 bp) regions, and two inverted repeat regions (IRs, 23,632bp each). A total of 129 genes are successfully annotated, including 84 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic relationships showed that Malus spectabilis ‘Guanghui’ is closely related to the species of Malus sieversii.